Retrospektif studi: Peranan kader kesehatan jiwa terkait kunjungan follow-up pasien gangguan jiwa ke Puskesmas - Evi Indrayana; Teguh Pribadi; Satrio Kusumo Lelono (Holistik Jurnal Kesehatan, 2020)
A retrospective evaluation: Follow-up of patients with severe mental illness and the role of community mental health workers among cadres of non-specialist health workersBackground : The default of regular treatment can cause a recurrence of patients with mental disorders. As an effort to increase participation in medicine, one of them is increasing the role of mental health cadres. Based on the results of a pre-survey study conducted in the work area of Way Mili Health Center in December 2018 - January 2019, found it out that 39 patients who actively took part in mental health programs were only 38.46%. And out of 5 mental health cadres, only 1 cadre has an ideal role and the remaining role is less ideal due to individual busyness and cadre incentives that are not under the responsibilities given.Purpose: Knowing the relationship between follow-up of patients with severe mental illness and the role of community mental health workers among cadres of non-specialist health workersMethod: This type of research is a retrospective evaluation, quantitative, analytic survey with a cross sectional approach. The population in this study was caregiver of patient with mental disorders. The questionnaire to determine the role of mental health cadres contains 15 questions and looking at medical records / treatment cards to find the consistency of follow up of patients at the public health centre. Data were analyzed by univariate and bivariate (chi square).Results : It is knowing that all cadres totaling 30 have a mean age of 35.33 years with a standard deviation of ± 3.05 with an age range of 30-40 years and are mostly educated in junior high school (70%) and work as housewives (60%). respondents where the role of cadres was in the low category and 66.7% with follow-up of patients in the irregular category (63.3%). The results of statistical tests on the education variable of the cadres p-value = 0.01; work p-value = 0.002 and patient visits p-value = 0.009 which means <α, it can be concluded that there is a relationship between the Role of Mental Health Cadres and Visits of Mental Disorders Patients in the Work Area of Way Mili Community Health Center, Gunung Protector District, East Lampung Regency, 2019. OR value 8,250 means respondents with low cadre roles have an 8 times greater risk of irregular visits when with high cadre roles.Keywords: A retrospective evaluation; Follow-up of patients; Severe mental illness; Role; CadresPendahuluan: Kekambuhan pasien dengan gangguan jiwa dapat diakibatkan karena gagalnya keberlanjutan pengobatan secara rutin. Sebagai upaya meningkatkan partisipasi dalam pengobatan salah satunya peningkatan peran kader kesehatan jiwa. Berdasarkan hasil pra survey penelitian yang dilakukan di wilayah kerja Puskesmas Way Mili Desember 2018 – Januari 2019 diketahui dari 39 pasien yang ikut aktif dalam berpartisipasi dalam program kesehatan jiwa hanya sebanyak 38,46%. Dan dari 5 kader kesehatan jiwa didapatkan hanya 1 kader yang berperan ideal dan sisanya berperan kurang ideal dikarenakan kesibukan individu dan insentif kader yang kurang sesuai dengan tanggung jawab yang diberikan.Tujuan : diketahui hubungan peran kader kesehatan jiwa dengan kunjungan pasien gangguan jiwa di wilayah kerja puskesmas Way Mili Kecamatan Gunung Pelindung Kabupaten Lampung Timur Tahun 2019.Metode : Jenis penelitian yang digunakan adalah evaluasi retrospektif, kuantitatif, survey analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah perawat pasien gangguan jiwa. Kuesioner untuk mengetahui peran kader kesehatan jiwa berisi 15 pertanyaan dan melihat rekam medis / kartu pengobatan untuk mengetahui konsistensi tindak lanjut pasien di puskesmas. Data dianalisis secara univariat dan bivariat (chi square).Hasil : Diketahui bahwa semua kader yang berjumlah 30 memiliki usia rata-rata 35,33 tahun dengan standar deviasi ± 3,05 dengan rentang usia 30-40 tahun dan sebagian besar berpendidikan SMP (70%) dan bekerja sebagai ibu rumah tangga (60%) ). responden dimana peran kader dalam kategori rendah dan 66,7% dengan tindak lanjut pasien dalam kategori tidak teratur (63,3%). Hasil uji statistik variabel pendidikan kader p-value = 0,01; kerja p-value = 0,002 dan kunjungan pasien p-value = 0,009 yang berarti <α, maka dapat disimpulkan bahwa ada hubungan antara Peran Kader Kesehatan Jiwa dengan Kunjungan Penderita Gangguan Jiwa di Wilayah Kerja Kesehatan Masyarakat Way Mili. Center, Kecamatan Gunung Protector, Kabupaten Lampung Timur, 2019. OR bernilai 8.250 artinya responden dengan peran kader rendah memiliki risiko 8 kali lebih besar untuk melakukan kunjungan tidak teratur bila dengan peran kader tinggi.